Antibiotic Prophylaxis to Prevent Surgical Site Infections in Children: A Prospective Cohort Study. Issue 2 (August 2015) - Khoshbin, Amir; So, Jeannette P.; Aleem, Ilyas S.; Stephens, Derek; Matlow, Anne G.; Wright, James G.
Abstract : Objective: To investigate the association between antibiotic prophylaxis (AP) and surgical-site infection in pediatric patients. Background: Surgical-site infections (SSIs) are a major cause of postoperative morbidity and mortality. Despite numerous studies in adults, benefit of AP in preventing SSIs in children is uncertain. Methods: Patients aged 0 to 21 years who underwent surgical procedures at a pediatric acute care hospital from April 1, 2009, to December 31, 2010, were assessed. Antibiotic prophylaxis indication and administration according to an evidence-based guideline were recorded. Complete compliance was defined as AP given, when indicated, within 60 minutes before incision. Surgical-site infections were identified using the Centers for Disease Control and Prevention criteria and documented in the medical records using the International Classification of Diseases, Tenth Revision . Multiple logistic regressions adjusting for age, sex, American Society of Anesthesiologists status, wound classification, admission status, surgical discipline, and surgical duration evaluated association of AP compliance and SSI. Results: Of 5309 patients for whom antibiotics were indicated, 3901 (73.5%) with complete compliance had an infection rate of 3.0%, whereas 1408 (26.5%) who were not compliant had an infection rate of 4.3% (adjusted relative risk: 0.7; 95% confidence interval: 0.5–0.9; P = 0.02). Of 4156 patients for whom antibiotics were not indicated, the 895 (21.5%) who received antibiotics had an infection rate of 1.7% compared with 0.7% in the 3261 (78.5%) who did not receive antibiotics (adjusted relative risk: 1.6; 95% confidence interval: 0.8–3.1; P = 0.18). Conclusions: In pediatric surgery, complete compliance with AP was associated with 30% decreased risk of SSI. Abstract : Supplemental Digital Content is Available in the Text.Surgical site infections are a major cause of postoperative morbidity and mortality, but benefit of antibiotic prophylaxis in children is uncertain. Association between compliance with antibiotic prophylaxis guidelines and surgical site infections was evaluated in 9465 patients at a pediatric acute care hospital. Appropriate antibiotic prophylaxis decreased risk of infection by 30%.